Effects of O7+ and Ni9+ swift heavy ions irradiation on polyacrylamide grafted Gum acacia thin film and sorption of methylene blue. (January 2015) - Kaith, B.S.; Sharma, Rachna; Sharma, Kashma; Choudhary, Sukriti; Kumar, Vijay; Lochab, S.P.
Abstract: Acrylamide was graft copolymerized onto Gum acacia using N, N ' -methylene-bis-acrylamide and potassium persulphate as a crosslinker-initiator system. Synthesized polymer film was irradiated with 80 MeV O 7+ and 100 MeV Ni 9+ ion beams at various fluences ranging from 1 × 10 11 to 5 × 10 12  ions cm −2 . Significant changes in property profile with respect to swelling, optical, chemical, structural, morphological and thermal properties were observed after irradiation. Percentage swelling was found to increase with the increase in ions fluence. Maximum percentage swelling (450%) was observed in case of Ni 9+ ion irradiated polymer film. The FTIR spectra showed variation in intensity of the typical bands and prominence of some bands indicated increase in amorphous region of polymer film after irradiation. This was also supported by X-ray diffraction studies. Structural modifications were further supported by scanning electron microscopy and thermogravimetric analysis. Additionally, the polymer films irradiated with SHIs with different ion fluencies were evaluated for methylene blue sorption behaviour. The irradiation effects of O 7+ ions were found to be similar to that of Ni 9+ ions. However, in case of irradiation with the ions having higher atomic number, the modifications induced were found to depend on the beam energy and the stopping power of the ion. The extent of modifications induced therefore, seems to have linear energy transfer dependence. Highlights: The effect of swift heavy ions irradiation on percentage swelling and dye adsorption behaviour were studied. Structural, optical, thermal, morphological and chemical changes after irradiation were investigated. Ion beam irradiation improves the swelling and sorption behaviour of GA-g-poly(AAm) films. The induced modifications were discussed on the basis of linear energy transfer of the ions.